Systematic Assessment of Gamma Hydroxybutyrate (GHB) Effects During and After Acute Intoxication - Kim, Susan Y. (2008)
We adapted and tested a previously published questionnaire battery eliciting sensory and cognitive symptoms during (acute) and immediately after (post-acute) GHB intoxication. Studying 125GHBusers, we assessed the instrument’s internal consistency using Cronbach’s alpha (CA) and responsiveness to change comparing acute and post-acute symptoms. The final 14-item battery demonstrated good internal consistency (CA ≥ 0.85, both acute and post-acute). The median symptom score (possible range 0–64) was 30 (acute) and 6 (post-acute; difference p < 0.001). This modified substance-specific symptom battery, which is easily administered, demonstrated excellent performance characteristics. It can be used to study GHB and, potentially, related drugs of abuse.